Document Validation using Blockchain: A validation scheme for natural persons documents - Meyer, João Vicente; Palma, Lucas Machado; Martina, Jean Everson (Anais Estendidos do Simpósio Brasileiro de Redes de Computadores e Sistemas Distribuídos (SBRC), 2020)
The great extension of Brazil's territory, combined with its demographics of more than 200 million inhabitants, results in a complex, slow and expensive notary system. Blockchain technologies can be of huge help in this scenario. It provides a decentralized peer-to-peer way of storing and validating documents. In this article, we start the discussion about a blockchain-based national notary system with means to store and validate the natural person's public documents. We prototype a solution, comprising of birth, marriage, divorce, and death documents/certificates. In the end, we present a comparison between the operational costs of the implemented prototype and the current notary system.